Premarital Sex Behavior Model with Lasso Generalized Linear Mixed Model and Group Lasso Generalized Linear Mixed Model - Khalilah Nurfadilah; Asfar; Khairil A. Notodiputro; Bagus Sartono; Azlam Nas (Statistika, 2023)
ABSTRACT Premarital sexual behavior is sexual behavior that is carried out between men and women without legal marriage. As the number of premarital sex increases, efforts need to take. One that can do is to identify the main factors contributing to reducing or increasing premarital sex behavior by a Regression model. In the context of sexual behavior, environmental influences cannot be ignored. GLMM is used to model data that is grouped into certain Groups, include environment effect that is modeled as mixed effect in GLMM. In terms of parsimony, the LASSO method can do selection variables. This research uses GLMM LASSO and GLMM Group LASSO as a model to approach the data. The best model that describes premarital sex behavior in South Sulawesi is the GLMM Group LASSO model based on the greatest AUC value. The variables that significantly influence the model are Type of Residence (X_1), Education Level (X_2), Literacy (X_3), Internet use (X_4), Knowledge of Contraceptive Methods (X_6), Health Insurance Ownership (X_7), Employment Status (X_8), Knowledge of Sexually Transmitted Diseases (X_9). By knowing the factors that influence premarital sex behavior, the government is expected to take the appropriate action for handling it.